Anticoagulant Micrurus venoms: Targets and neutralization. (1st February 2021) - Dashevsky, Daniel; Bénard-Valle, Melisa; Neri-Castro, Edgar; Youngman, Nicholas J.; Zdenek, Christina N.; Alagón, Alejandro; Portes-Junior, José A.; Frank, Nathaniel; Fry, Bryan G.
Highlights: Multiple coral snake ( Micrurus ) species possess anticoagulant venom. Micrurus laticollaris venom is especially anticoagulant in plasma. There is no strong phylogenetic pattern in the effect on clotting time. Coralmyn antivenom is not effective against the anticoagulant venoms. Varespladib is extremely effective against the anticoagulant venoms. Abstract: Snakebite is a neglected tropical disease with a massive global burden of injury and death. The best current treatments, antivenoms, are plagued by a number of logistical issues that limit supply and access in remote or poor regions. We explore the anticoagulant properties of venoms from the genus Micrurus (coral snakes), which have been largely unstudied, as well as the effectiveness of antivenom and a small-molecule phospholipase inhibitor—varespladib—at counteracting these effects. Our in vitro results suggest that these venoms likely interfere with the formation or function of the prothrombinase complex. We find that the anticoagulant potency varies widely across the genus and is especially pronounced in M. laticollaris . This variation does not appear to correspond to previously described patterns regarding the relative expression of the three-finger toxin and phospholipase A2 (PLA2 ) toxin families within the venoms of this genus. The coral snake antivenom Coralmyn, is largely unable to ameliorate these effects except for M. ibiboboca . Varespladib on the other hand completely abolished the anticoagulant activity of every venom. This is consistent with the growing body of results showing that varespladib may be an effective treatment for a wide range of toxicity caused by PLA2 toxins from many different snake species. Varespladib is a particularly attractive candidate to help alleviate the burden of snakebite because it is an approved drug that possesses several logistical advantages over antivenom including temperature stability and oral availability.